Images of the Muslim Woman and the Construction of Muslim Identity: The Essentialist Paradigm Journal for Religion, Film and Media - Elham Manea (Journal for Religion, Film and Media, 2016)
This article argues that much of the postmodern discourse on the Muslim woman and her veil is symptomatic of what I call the "essentialist paradigm". The world is seen through the prism of a group's religious/cultural identity and eventually constructs a Muslim identity - and with it an image of the Muslim Woman. The image of the oppressed veiled Muslim Woman and the treatment of a piece of cloth as synonymous with her whole identity and being are products of this paradigm of thought. Using an interdisciplinary approach that combines discourse analysis and a case study of the construction of the British Muslim community, this article argues that the essentialist paradigm ignores the context of its subject matter with all its accompanying power structures, political and social factors, and the roles played by both the state and fundamentalist Islam in constructing a Muslim identity and with it the Muslim Woman and her dress code.